(untitled) (Research, Society and Development, 2022)
Objective: Evaluate the cytotoxicity in human osteoblastic cells and antimicrobial activity in different root canal sealers in vitro. Methods: BioRoot RCS, TotalFill BC Sealer, and Bio-C Sealer were used in experimental groups, and AH Plus was used as a control. Human osteoblast-like cells and MTT quantitative colorimetric assay were used to evaluate cytotoxicity. Saos-2 cells were exposed to undiluted sealer extracts for 24 h. The supernatant was then collected and the formazan crystals resulting from MTT reduction were dissolved in pure dimethyl sulfoxide. Absorbance was measured in an automated spectrophotometer at a wavelength of 540 nm. Antimicrobial activity was analyzed by the direct contact test using a polymicrobial biofilm composed of Enterococcus faecalis, Candida albicans, and Streptococcus mutans. At 24, 48, and 72 h, colony-forming units were counted on agar plates. A nonparametric Kruskal-Wallis test was used for the statistical analysis. The level of significance was set at 5%. Results: AH Plus showed the lowest cytotoxicity after 24 h, with a significant difference in relation to BioRoot RCS and Bio-C Sealer (p ≤ 0.01). There was no significant difference in cytotoxicity between TotalFill BC Sealer and Bio-C Sealer (p > 0.05). At 24 h, TotalFill BC Sealer and AH Plus showed the least microbial growth compared to Bio-C Sealer (p < 0.05). At 48 and 72 h, there were no significant differences between sealers (p > 0.05). Conclusions: AH Plus had the lowest cytotoxicity. TotalFill BC Sealer and AH Plus yielded greater reductions in microbial counts in the first 24 h compared to Bio-C Sealer. Clinical Relevance: 2c.